2019
DOI: 10.1109/access.2019.2949074
|View full text |Cite
|
Sign up to set email alerts
|

Stock Volatility Prediction by Hybrid Neural Network

Abstract: Stock price volatility forecasting is a hot topic in time series prediction research, which plays an important role in reducing investment risk. However, the trend of stock price not only depends on its historical trend, but also on its related social factors. This paper proposes a hybrid time-series predictive neural network (HTPNN) that combines the effection of news. The features of news headlines are expressed as distributed word vectors which are dimensionally reduced to optimize the efficiency of the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Combining techniques (ensemble) using several learning methods [46], [47], [48], [49], [31], [11], [4], [5]. Using boost algorithm (Boosting Method) [50], [51], [13], [34], [52]. Added a feature selection method [53], [54], [55], [36], [56].…”
Section: Proposed Methods Improvements and Modification For Stock Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining techniques (ensemble) using several learning methods [46], [47], [48], [49], [31], [11], [4], [5]. Using boost algorithm (Boosting Method) [50], [51], [13], [34], [52]. Added a feature selection method [53], [54], [55], [36], [56].…”
Section: Proposed Methods Improvements and Modification For Stock Predictionsmentioning
confidence: 99%
“…Several studies have proven that optimized parameters and hyper-parameters can improve model performance than models without optimization. Research [36] in hyper-parameter XGBoost algorithm optimized using Genetic Algorithm, [51] LSTM neural network parameters optimized using Random Search, [5] hyperparameter Random Forest algorithm optimized using the Grid Search method, [52] experimented with four algorithms namely ANN, SVM, RF, and LR which were optimized using the Grid Search method, as well as [43] the Deep Naural Network that was built optimized using the grid Search method.…”
Section: Parameter and Hyper-parameter Optimizationmentioning
confidence: 99%
“…Moreover, there have been various studies on text mining applications to financial markets due to considerable influence of text news on the markets. Wang et al [25] propose a hybrid time-series predicted neural network for forecasting stock volatility. Crone and Koeppel [26] explore efficacy of using sentiment indicators as a predictor for foreign exchange rates.…”
Section: A Level Factor Representingmentioning
confidence: 99%
“…In addition, NN does not require assumptions regarding the distribution of data while it can learn from the data. The NN models have recently been applied to predict volatility series in many fields [11], [38], [45], [52]. In the case of the exchange rate volatility forecasting, Panda and Narasimhan [6] found that Neural Network (NN) has a better exchange rate forecasting performance for not only in-sample but also outof-sample period, compared to the linear regression and random walk models.…”
Section: Related Workmentioning
confidence: 99%